A 3D numerical and experimental parametric study of wave-induced scour around large bluff body structures. (15th December 2022) - Lancaster, Orrin; Cossu, Remo; Wilson, Mylo; Baldock, Tom E.
Abstract: This is the first study to undertake a comprehensive parametric study of wave-induced scour around a large bluff body structure, and also presents experimental data to validate a CFD model for wave-induced scour around the structure. A parametric study is undertaken using the REEF3D CFD model for varying incident wave condition (depth, wave amplitude, frequency, and direction), structure geometry (width, length, and corner curvature), and sediment size. The numerical model is validated against experimental datasets, demonstrating that the model can accurately replicate scour around large bluff body structures. Two new equations are proposed for prediction of non-dimensional equilibrium scour depths at the front and back corners of a large bluff body structure using the Keulegan-Carpenter (KC) number based on 18 and 24 datapoints respectively. The equations are valid within the following limits: 0.37 ≤ KC ≤ 1.75, 0.10 ≤ B/λ p and 0.14 ≤ L/λ p, where B and L are the structure width and streamwise length, and λ p is the peak wave length. It is further demonstrated that the non-dimensional scour depth does not vary significantly with the sediment size (for 0.075 ≤ θ ≤ 0.117 where θ is the Shields parameter), or the structure width/length for the limits stated above. Highlights: Parametric study of wave-induced scour around a large bluff body structure. Numerical model validated against original and existing experimental datasets. Two new equations proposed for scour prediction at corners of a large bluff body. Equilibrium scour depth for live-bed regime shown not to vary with sediment size.